2022
DOI: 10.3390/ijerph19063334
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Health in U.S. Shift Workers: Insights from a Cross-Sectional Study (NHANES)

Abstract: Working outside of regular daytime hours is increasingly common in current societies and poses a substantial challenge to an individual’s biological rhythm. Disruptions of the gastrointestinal tract’s circadian rhythm and poor dietary choices subsequent to shiftwork may predispose the shift workforce to an increased risk of gastrointestinal disorders, including constipation, peptic ulcer disease, and erosive gastritis. We investigated bowel health in a US population of shift workers, using data from the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…In a previous study, we discussed the association between shift work and food insecurity in terms of limited access to adequate food for active, healthy living. Our analysis revealed that a significantly higher proportion of shift workers reported receipt of food stamps and concerns about running out of food, as compared to day workers (Storz et al , 2022a). A poor diet has been suggested as one of the major culprits for the detrimental health effects induced by shift work, and several experts highlighted that unhealthy eating “could legitimately be considered a new form of occupational hazard” (TPIM Editors, 2011).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…In a previous study, we discussed the association between shift work and food insecurity in terms of limited access to adequate food for active, healthy living. Our analysis revealed that a significantly higher proportion of shift workers reported receipt of food stamps and concerns about running out of food, as compared to day workers (Storz et al , 2022a). A poor diet has been suggested as one of the major culprits for the detrimental health effects induced by shift work, and several experts highlighted that unhealthy eating “could legitimately be considered a new form of occupational hazard” (TPIM Editors, 2011).…”
Section: Introductionmentioning
confidence: 70%
“…A similar approach has been used by Wirth et al (2014) in a related analysis. The rationale behind this approach is explained in one of our previous publications (Storz et al , 2022b). The current analysis is part of a larger series of investigations targeting a better understanding of nutrition-related disorders in shift workers (Storz et al , 2022a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation